The Effect of Location Class Category and Pipe Wall Thickness on Risk Level Onshore Pipeline Oil - Zakki Fuadi Emzain; Makhmudul Fikri; Satworo Adiwidodo; Ratna Monasari; Talifatim Machfuroh (Politeknik Negeri Lhokseumawe, 2024)
Pipelines are essential infrastructure for efficient oil and gas production operation, necessitating their continuous and reliable functionality in all locations and circumstances. Nevertheless, the pipeline can fail during operation due to multiple detrimental variables. This study evaluated the impact of the location classification category and pipe wall thickness on the risk level of onshore pipelines. The risk assessment method employed was a semiquantitative approach derived from the reference